Cost and Affordability of Nutritious Diets at Retail Prices: Evidence from 744 foods in 159 Countries. - Alemu, Robel.; Bai, Yan.; Block, Steven.; Headey, Derek.; Masters, William. (Tufts University. Tisch Library., 2020)
Many policies and programs aim to bring nutritious diets within reach of the poor. This paper uses retail prices and nutrient composition for 744 widely-consumed food and beverage items to compute the daily cost of meeting nutrient requirements for an active and healthy life, for comparison with the subsistence cost of dietary energy, measurement of affordability relative to per-capita earnings, and analysis of stylized facts about how cost and affordability relates to nutrition outcomes and economic development around the world. We find that the minimum cost of adequate nutrition exceeds the minimum cost of adequate energy intake by a factor of 2.5-3.8, with substantial variation both access and within national income groups. Relative to average household expenditures, adequate nutrition of least affordable in Sub-Saharan Africa, and the most affordable in North America. In absolute terms, the minimum cost of adequate nutrition in many poor countries exceeds the global $1.90/day poverty line. Costs are lower in higher-income countries, which we explain as a function of infrastructure and the efficiency of agricultural marketing and retail food systems.; Poster presented by Robel Alemu at the Tufts Graduate Student Council's 24th Graduate Student Research Symposium, March 6, 2020.